2012
DOI: 10.2215/cjn.10010911
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Mechanisms of Intradialytic Hypertension

Abstract: SummaryBackground and objectives Intradialytic hypertension may be caused by an impaired endothelial cell response to hemodialysis. Carvedilol has been shown to improve endothelial cell function in vivo and to block endothelin-1 release in vitro. This study hypothesized that carvedilol would improve endothelial cell function and reduce the occurrence of intradialytic hypertension.Design, setting, participants, & measurements A prospective 12-week pilot study of carvedilol titrated to 50 mg twice daily was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 26 publications
2
49
3
1
Order By: Relevance
“…Endothelial cell dysfunction and sympathetic hyperactivity may contribute to higher home, predialysis, and intradialytic BPV, and they may potentially be therapeutic targets with therapies, such as carvedilol or renal denervation. [26][27][28] Our findings have several implications for clinical practice and research. It is important for clinicians to recognize BPV in their dialysis patients as a risk factor for adverse CVevents.…”
Section: Discussionmentioning
confidence: 82%
“…Endothelial cell dysfunction and sympathetic hyperactivity may contribute to higher home, predialysis, and intradialytic BPV, and they may potentially be therapeutic targets with therapies, such as carvedilol or renal denervation. [26][27][28] Our findings have several implications for clinical practice and research. It is important for clinicians to recognize BPV in their dialysis patients as a risk factor for adverse CVevents.…”
Section: Discussionmentioning
confidence: 82%
“…For example, carvedilol, a β-blocker with vasodilating properties, was shown to improve endothelial dysfunction in vivo 50 and block endothelin-1 release in vitro. 51 In an uncontrolled study, 4 in 25 patients with intradialytic hypertension, carvedilol treatment was associated with an improvement in endothelium-dependent flow-mediated vasodilatation, 4 which was accompanied by reduced occurrence of intradialytic hypertensive episodes during follow-up and with a significant fall (7 mm Hg) in 44-hour ambulatory SBP. 4 Therefore, antihypertensive agents exerting beneficial actions on endothelium, such vasodilating β-blockers, may be of benefit for patients with intradialytic hypertension.…”
Section: Treatment Of Endothelial Dysfunctionmentioning
confidence: 98%
“…2,3 The BP rise during dialysis has a complex mechanistic background and is multifactorial in nature. 2,4 Herein, we provide a systematic review of the epidemiology and pathogenesis of intradialytic hypertension and key recommendations for the management of this neglected dialysis-related complication. The search strategy and selection criteria used for this review are reported in Table S1 in the online-only Data Supplement and Figure S1.…”
mentioning
confidence: 99%
“…However, the phenomenon of intradialytic hypertension is complex and incompletely understood; pilot studies suggest that endothelial dysfunction may be operative in its pathogenesis. 78 Home BP measurement is a practical way to measure and manage hypertension among HD patients. The targets of therapy using home BP monitoring will need to be defined in future trials.…”
Section: Diagnosismentioning
confidence: 99%